Diverse accounting standards on disclosures of Islamic financial transactions Prospects and challenges of narrowing gaps - Ahmed, H; Ariffin, FAT; Karbhari, Y; Zurina Shafii (Emerald Group Publishing Ltd, 2024)
Indexed WOS/SCOPUS/ERA